An Investigation of Protonic and Oxide Ionic Conductivities at the Interfacial Layers in SDC-LNC Composite Electrolytes. (10th September 2016) - Li, Chuanming; Zeng, Yanwei; Wang, Zhentao; Xu, Fei; Ye, Zhupeng; Shi, Rui
Abstract: SDC (Sm0.2 Ce0.8 O1.9 )-LNC ((Li0.52 Na0.48 )2 CO3 ) nanocomposites with various LNC volume fractions (0.0, 0.3, 0.4, 0.5, 0.6, 0.7 and 1.0) and MgO-50LNC composites were prepared by prefiring and sintering at different temperatures. The XRD, FESEM and TEM techniques were employed to characterize their phase components and microstructures. The AC impedance spectroscopy and DC polarization method were used to measure their electrical conductivities under different conditions. It has been found that the carbonate phase in the MgO-LNC composites is homogeneously crystallized, whereas amorphous carbonate is always identified in the SDC-LNC composites and shown to form an interface layer of ∼6 nm in thickness at the surface of SDC crystallites due to the strong interactions between SDC and LNC phases. The protonic, oxide ionic and overall ionic conductivities of LNC phase were measured at the different temperatures from 450 to 650 °C and then adopted to study the contributions of the interfacial interaction between SDC and LNC phase to the enhanced electrical conductivity of SDC-50LNC composites. The interfacial interactions were found to significantly enhance the protonic and oxide ionic conductivities in the SDC-LNC composites regardless of the remarkable suppressing effect on the migrations of metal ions as the majority mobile charged species in the molten LNC phase. Furthermore, based on a microstructural model of randomly-packed SDC/LNC composite particles and the Maxwell-Garnet mixture rule, the protonic and oxide ionic conductivities of the interface layer was successfully found to reach as high as 97 mS/cm and 46 mS/cm at 650 °C, respectively, through a non-linear least-squares data analysis.